Lentiviral Vector Induced Insertional Haploinsufficiency of Ebf1 Causes Murine Leukemia - Heckl, Dirk (Nature Publishing Group, 2012)
Integrating vectors developed on the basis of various retroviruses have demonstrated therapeutic potential following genetic modification of long-lived hematopoietic stem and progenitor cells. Lentiviral vectors (LV) are assumed to circumvent genotoxic events previously observed with γ-retroviral vectors, due to their integration bias to transcription units in comparison to the γ-retroviral preference for promoter regions and CpG islands. However, recently several studies have revealed the potential for gene activation by LV insertions. Here, we report a murine acute B-lymphoblastic leukemia (B-ALL) triggered by insertional gene inactivation. LV integration occurred into the 8th intron of Ebf1, a major regulator of B-lymphopoiesis. Various aberrant splice variants could be detected that involved splice donor and acceptor sites of the lentiviral construct, inducing downregulation of Ebf1 full-length message. The transcriptome signature was compatible with loss of this major determinant of B-cell differentiation, with partial acquisition of myeloid markers, including Csf1r (macrophage colony-stimulating factor (M-CSF) receptor). This was accompanied by receptor phosphorylation and STAT5 activation, both most likely contributing to leukemic progression. Our results highlight the risk of intragenic vector integration to initiate leukemia by inducing haploinsufficiency of a tumor suppressor gene. We propose to address this risk in future vector design.